The whistleblower's dilemma : Snowden, Silkwood and their quest for the truth - Rashke, Richard L. (2015)
The author weaves between the lives of these two controversial figures and creates a narrative context for a discussion of what constitutes a citizen's duty to reveal or not to reveal. He asks the question: can our government regulators, our politicians, our military-intelligence and our profit-oriented corporations be trusted to protect us from harm as well as safeguard our privacy?
Includes bibliographical references (pages 191-205).
Keywords: Snowden, Edward J., -- 1983-; Silkwood, Karen, -- 1946-1974.; Silkwood, Karen, -- 1946-1974.; Snowden, Edward J., -- 1983-; Leaks (Disclosure of information) -- United States; Whistle blowing -- United States; Leaks (Disclosure of information); Whistle blowing; United States